Application of CRISPR screen in mechanistic studies of tumor development, tumor drug resistance, and tumor immunotherapy - Li, Min; Sun, Jin; Shi, Guohai (Frontiers in Cell and Developmental Biology, 2023)
Tumor is one of the biggest threats to human health. Though tumor therapy has been dramatically advanced by the progress of technology and research in recent decades, it is still far from expectations. Thus, it is of great significance to explore the mechanisms of tumor growth, metastasis, and resistance. Screen based on Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-CRISPR-associated protein (Cas) 9 gene editing technology are powerful tools for exploring the abovementioned facets. This review summarizes the recent screen performed in cancer cells and immune cells in the tumor microenvironment. The screens in cancer cells mainly focus on exploring the mechanisms underlying cancer cells’ growth, metastasis, and how cancer cells escape from the FDA approved drugs or immunotherapy. And the studies in tumor-associated immune cells are primarily aimed at identifying signaling pathways that can enhance the anti-tumor function of cytotoxic T lymphocytes (CTLs), CAR-T cells, and macrophages. Moreover, we discuss the limitations, merits of the CRISPR screen, and further its future application in tumor studies. Importantly, recent advances in high throughput tumor related CRISPR screen have deeply contributed to new concepts and mechanisms underlying tumor development, tumor drug resistance, and tumor immune therapy, all of which will eventually potentiate the clinical therapy for tumor patients.